Cystatin C as a Biomarker for Identifying High-Risk Patients with Acute Coronary Syndrome: An Observational Study - Xinlin Xiong MD; Li Yuan MB; Xiaobin Long MM; Minsheng An MB; Shen Huang MM; Liang Liu MB (Clinical and Applied Thrombosis/Hemostasis)
Background Cystatin C is a cysteine protease inhibitor, synthesized by nucleated cells, and released into various body fluids. Lots of studies have reported an association between cystatin C and atherosclerotic cardiovascular disease. However, the association of cystatin C with high-risk patients with acute coronary syndrome(ACS) has not been well studied. In this study, we investigated potential association of cystatin C with high-risk patients with ACS, and assessed whether cystatin C provide discriminating power of clinical risk stratification in patients with ACS. Methods We enrolled 219 patients with ACS in the present study. The cystatin C concentration was measured in clinical laboratory. The global registry of acute coronary events (GRACE) scores was calculated to assess risk stratification. The high-risk patients with ACS were defined based on GRACE scores and killip classification. Results The cystatin C levels were significantly higher in high-risk patients compared to non-high-risk patients, both in the overall ACS group and its subtypes, including non-ST elevation ACS (NSTE-ACS) and ST elevation ACS (STE-ACS)( P  < 0.05). The receiver operating characteristic (ROC) curve analysis showed that cystatin C had a discriminative performance for identifying high-risk patients across these groups( P  < 0.05). After adjusting for potential confounders, multivariate logistic regression confirmed that the elevated cystatin C levels were independently associated with high-risk patients with ACS( P  < 0.05). Conclusions The cystatin C was obviously elevated in high-risk group in the patients with ACS and its subgroups. Cystatin C appears to be a valuable biomarker for distinguishing and predicting high-risk patients with ACS, suggesting its relevance in clinical risk stratification.